ANALISIS HUKUM PENGGABUNGAN PERKARA KORUPSI DAN MONEY LAUNDERING DALAM SISTEM PERADILAN DI INDONESIA - Chandra Purnama; Bismar Nasution; Sunarmi Sunarmi; Mahmud Mulyadi (Universitas Sumatera Utara, 2016)
ABSTRACT In Indonesia has been increasingly widespread practice of corruption and even to all aspects of life, both at central and local levels. Corruption is referred to as a crime against humanity because it has resulted in poverty and misery of the people. Corruption practices often followed by the Money Laundering Practice, money laundering practices today are very often carried out on the money earned from the evil of corruption. Corruption with Money Laundering has a relationship or association which is very fundamental. It can clearly be seen in article 2, paragraph 1 of Law - Law No. 8 of 2010 on the prevention and eradication of money laundering. In the Act itself known with a term called